PENINGKATAN KEMAMPUAN MENULIS AKSARA JAWA DENGAN METODE ULUM TUAN BAIK MENGGUNAKAN MEDIA LUSAPA - Tri Muryanti (Jurnal Didaktika Pendidikan Dasar, 2019)
This learning innovation study aims to find out whether the method of Ulum Tuan Baik with Lusapa media can improve the writing skills of Javanese script and how the method of Ulum Tuan Baik with Lusapa media can improve the writing skills of Javanese script to the students of Class VII A UPTD SMPN 2 Tarokan in the school year of 2017/2018. The data analysis method that is used in this study is quantitative and qualitative, using test instruments to obtain quantitative data and non-test instruments to obtain qualitative data. The results of the study have obtained that the Ulum Tuan Baik method with Lusapa media is proven to be able to improve the ability of the students to write sentences using Javanese script with its sandhangan and pasangan. Improvement of the writing skills of Javanese script seen from the class average value which has increased at each stage of the study. Class average value on the pre-action stage is 67.96. On the first cycle, it has increased by 75.93%  and on the second cycle, it has increased by 82.96%.